Fracture Resistance of CAD/CAM Lithium Disilicate and 3D-Printed Resin Crowns with Varying Occlusal Thickness: An In Vitro Study - Tartuk, Bulent Kadir; Altintas, Eyyup; Sengul, Melike (Mdpi, 2026)
This in vitro study evaluated the fracture resistance of CAD/CAM-fabricated lithium disilicate and 3D-printed resin crowns with varying occlusal thicknesses (0.5, 1.0, and 1.5 mm) following thermomechanical aging. Sixty extracted human molars were assigned to six experimental groups (n = 10), categorized by crown material and occlusal thickness. The crowns were fabricated using CAD/CAM technology in accordance with the manufacturer's protocol. All specimens underwent thermomechanical aging, which consisted of thermocycling between 5 and 50 degrees C (5500 cycles) combined with mechanical loading of 50 N at 1.6 Hz for 75,000 cycles. The fracture loads were measured using a universal testing machine, and the failure modes were assessed using scanning electron microscopy. Statistical evaluation was performed using two-way analysis of variance with Tukey's post hoc test (alpha = 0.05). Both the material type and occlusal thickness had a statistically significant effect on fracture resistance (p < 0.001). Lithium disilicate crowns exhibited higher fracture loads than 3D-printed resin crowns independent of occlusal thickness. Although the fracture resistance of 3D-printed resin crowns was lower, specimens with occlusal thicknesses >= 1.0 mm exhibited fracture loads exceeding average physiological masticatory forces, suggesting that 3D-printed resin crowns may represent a clinically acceptable option for conservative posterior restorations. In contrast, crowns with an occlusal thickness of 0.5 mm demonstrated fracture resistance values below the reported functional masticatory loads. Additionally, the proportion of repairable fractures increased with increasing occlusal thickness for both materials. Overall, the findings suggest that an occlusal thickness of at least 1.0 mm may represent a reliable threshold for posterior restorations, whereas a thickness of 0.5 mm may be insufficient to withstand functional occlusal loads in molar regions.
Keywords: CAD/CAM crowns; 3D printing; additive manufacturing; conservative dentistry; occlusal thickness; dental materials